2011
DOI: 10.1371/journal.pone.0024802
|View full text |Cite
|
Sign up to set email alerts
|

Present Limits to Heat-Adaptability in Corals and Population-Level Responses to Climate Extremes

Abstract: Climate change scenarios suggest an increase in tropical ocean temperature by 1–3°C by 2099, potentially killing many coral reefs. But Arabian/Persian Gulf corals already exist in this future thermal environment predicted for most tropical reefs and survived severe bleaching in 2010, one of the hottest years on record. Exposure to 33–35°C was on average twice as long as in non-bleaching years. Gulf corals bleached after exposure to temperatures above 34°C for a total of 8 weeks of which 3 weeks were above 35°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 20 publications
6
131
2
Order By: Relevance
“…Knowledge gained from these experiments should also help evaluate whether Gulf corals could potentially be used for assisted migration in reef restoration projects outside their natural habitat (Riegl et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge gained from these experiments should also help evaluate whether Gulf corals could potentially be used for assisted migration in reef restoration projects outside their natural habitat (Riegl et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that adaptation to different thermal environments has a long-term influence on the potential of the P. lobata to respond to episodes of high temperature and that the samples from Abu Dhabi are more tolerant of the high temperatures in experimental treatments. Since Gulf corals are increasingly endangered in their native habitat (Burt et al 2008(Burt et al , 2011, it was suggested that these uniquely thermally adapted genotypes should be conserved, or perhaps even transplanted, for the benefit of other reefs that are expected to experience similar temperature extremes by 2099 as those currently experienced by the Gulf (Riegl et al, 2011). Such a strategy would only make sense if the thermal tolerance of Gulf corals was indeed retained ex situ.…”
Section: Temperature Challenge Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, those systems already precariously positioned at the edge of the frontier (v 2 ) have few additional mechanisms for adapting and, thus, are most in danger of crossing the edge into an unsafe operating space. For example, montane, boreal forest and coral reef ecosystems all persist at the edge of their climatological limits and, thus, have little capacity to adapt to climatic change [33][34][35][36]. Similarly, poverty has been identified as a key factor influencing the vulnerability of human populations to climate variability and change [37,38].…”
Section: Defining the Frontiermentioning
confidence: 99%
“…This notably explains why the majority of Acropora bleaching events in the highly oscillating thermal environment of the Persian Gulf have occurred during positive temperature anomalies (Riegl 2002;Sheppard & Loughland 2002;Riegl 2003;Burt et al 2008;Riegl 2011), while few bleachings followed negative thermal stresses (Shinn 1975;Coles & Fadlallah 1990). Current projections under RCP (Representative Concentration Pathways) 8.5 predict that seawater temperature increase by 4.26°C over 2010-2099 in the Persian Gulf (Hoegh-Guldberg et al 2014).…”
Section: Discussionmentioning
confidence: 99%